Spillovers Through Banking Centers : A Panel Data Analysis. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
To test the role of bank lending in transmitting currency crisis we examine a panel of BIS data on bank flows to 30 emerging markets disaggregated by 11 banking centers. We find that bank exposures to a crisis country help predict bank flows in third countries after the Mexican and Asian crisis, but not after the Russian crisis. In the latter, there is evidence of a generalized outflow from emerging markets, rather than outflows linked to prior exposure to Russia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet